2021
DOI: 10.3390/ijms22094766
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Small-Molecule Inhibitors in Blocking the PD-1/PD-L1 Pathway through PD-L1 Dimerization

Abstract: Programmed cell death-1 (PD-1), which is a molecule involved in the inhibitory signal in the immune system and is important due to blocking of the interactions between PD-1 and programmed cell death ligand-1 (PD-L1), has emerged as a promising immunotherapy for treating cancer. In this work, molecular dynamics simulations were performed on complex systems consisting of the PD-L1 dimer with (S)-BMS-200, (R)-BMS-200 and (MOD)-BMS-200 (i.e., S, R and MOD systems) to systematically evaluate the inhibitory mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 62 publications
(95 reference statements)
6
22
0
Order By: Relevance
“…The pocket of the EGCG system was surrounded by residues A Phe19, A Thr20, A Ala121, A Asp122, A Tyr123, A Lys124, B Ile54, B Tyr56, B Gln66, B Val68 and B Met115, among which the sidechain of B Gln66 was near the O37 atom of EGCG and the others neighbored the aromatic rings of EGCG. Briefly, the interaction modes between the PD-L1 dimer and food-derived compounds were in good concordance with those of the PD-L1 dimer and BMS small-molecules, as well as the [1,2,4] triazolo [4,3-a] pyridines inhibitors [40][41][42][43][44][45]. In particular, the residues located at the binding pockets-Ile54, Tyr56, Met115, Ala121 and Tyr12-were highly conservative.…”
Section: Nonbonded Interactionssupporting
confidence: 53%
“…The pocket of the EGCG system was surrounded by residues A Phe19, A Thr20, A Ala121, A Asp122, A Tyr123, A Lys124, B Ile54, B Tyr56, B Gln66, B Val68 and B Met115, among which the sidechain of B Gln66 was near the O37 atom of EGCG and the others neighbored the aromatic rings of EGCG. Briefly, the interaction modes between the PD-L1 dimer and food-derived compounds were in good concordance with those of the PD-L1 dimer and BMS small-molecules, as well as the [1,2,4] triazolo [4,3-a] pyridines inhibitors [40][41][42][43][44][45]. In particular, the residues located at the binding pockets-Ile54, Tyr56, Met115, Ala121 and Tyr12-were highly conservative.…”
Section: Nonbonded Interactionssupporting
confidence: 53%
“…Notably, after the 100 ns MD simulation, a decrement in the Δ G Bind Solv GB was noted and no substantial difference was observed in the Δ G Bind Lipo energy terms. Similar energy dissociation components were previously noted to contribute to the stability of the docked complexes of the PD-L1 protein [ 79 , 80 ]. Furthermore, reduction in net ligand strain energy was also noted following 100 ns MD simulation in each complex in comparison to the respective docked poses, suggesting the favorable contribution to the protein–ligand complex stability after 100 ns MD simulation ( Figure 7 ).…”
Section: Resultssupporting
confidence: 73%
“…Zhong et al generated a pharmacophore model based on BMS small molecule inhibitors, which consisted of one hydrogen bond donor, three hydrophobic points, and one positive ionizable point, and identified residues of PD-L1: Ile54, Tyr56, Val68, Met115, and Ala121 were involved in generating hydrophobic interactions, and Asp122 and Lys124 were involved in forming hydrogen bonds [ 33 ]. Guo et al investigated the inhibitory mechanism of PD-L1 dimer/BMS-200-related small molecule inhibitors by molecular dynamics simulation [ 34 ]. It was found that the inhibitors mainly bound to the key residues Ile54, Tyr56, Met115, Ala121, and Tyr123 on the PD-L1 dimer with non-polar interactions, and induced conformational changes in key residues.…”
Section: Introductionmentioning
confidence: 99%